Restoration goals: Why are fauna still overlooked in the process of recovering functioning ecosystems and what can be done about it? - Cross, Sophie; Bateman, Bill; Cross, Adam (WILEY, 2020)
Despite the evidence that fauna play complex and critical roles in ecosystems (e.g. pollination and nutrient cycling) and the knowledge that they need to be considered in restoration, fauna often remain poorly represented in restoration goal setting, monitoring and assessments of restoration success. Fauna clearly are integral to the aspirations of achieving full ecosystem recovery. However, over-reaching assumptions about the unassisted return of fauna to restored sites, low investment in fauna monitoring, and minimal consideration of the requirements for fauna monitoring in regulatory guidance and standards appear to have led to the historically vegetation-centric approaches to rehabilitation and ecological restoration. We argue that ecological complexities render assumptions of unassisted fauna return inappropriate in many situations and may represent a missed opportunity to enhance ecological outcomes and improve restoration trajectories. We advocate for greater consideration of fauna as facilitators of ecological restoration and, particularly for well-funded projects, for monitoring to place greater emphasis on examining the behaviour and resilience of restored fauna communities. There is a clear need for both industry and regulators to recognise that fauna can be crucial facilitators of restoration and appreciate that the return and monitoring of functional faunal communities can be costly, challenging and may require detailed study across a wide range of taxonomic groups. Failure to advance from business as usual models may risk leaving a legacy of ostensibly functional, but biodiversity-depauperate, restored ecosystems.